Spy High : mission one - Butcher, A. J. (New York : Little, Brown, 2004)
As students at a special high school that trains them to be secret agents, six teenagers struggle to complete the training exercises as a team before being sent out into the field to sink or swim.
Young Adult
Young Adult
Bulletin (Center for Children's books)
Kliatt
Keywords: Interpersonal relations -- Fiction; High schools -- Fiction; Spies -- Fiction; Schools -- Fiction; Adventure and adventurers -- Fiction; Interpersonal relations -- Fiction; High schools -- Fiction; Spy stories; School stories; Adventure fiction